Carbon dioxide-based facile synthesis of cyclic carbamates from amino alcohols. Issue 25 (12th March 2018) - Niemi, Teemu; Fernández, Israel; Steadman, Bethany; Mannisto, Jere K.; Repo, Timo
Abstract : Selective, straightforward, and efficient synthesis of cyclic carbamates from CO2 and amino alcohols. Abstract : We report herein a straightforward general method for the synthesis of cyclic carbamates from amino alcohols and carbon dioxide in the presence of an external base and a hydroxyl group activating reagent. Utilizing p -toluenesulfonyl chloride (TsCl), the reaction proceeds under mild conditions, and the approach is fully applicable to the preparation of various high value-added 5- and 6-membered rings as well as bicyclic fused ring carbamates. DFT calculations and experimental results indicate a SN 2-type reaction mechanism with high regio-, chemo-, and stereoselectivity.